Impact of age on the toxicity of immune checkpoint inhibition. Issue 2 (8th October 2020) - Samani, Amit; Zhang, Shuai; Spiers, Laura; Mohamed, Ali Abdulnabi; Merrick, Sophie; Tippu, Zayd; Payne, Miranda; Faust, Guy; Papa, Sophie; Fields, Paul; Van Hemelrijck, Mieke; Josephs, Debra H
Abstract : Indications for immune checkpoint inhibitor therapy are increasing. As the population ages, many patients receiving such drugs will be older adults. Such patients are under-represented in clinical trials, and therefore the safety of immune checkpoint inhibitors in this population has not been adequately assessed. A retrospective multicenter analysis of toxicities was performed in patients with advanced or metastatic solid cancers receiving anti-programmed cell death protein 1 (anti-PD-1) and/or anti-CTLA4 antibodies across three age cohorts (<65 years, 65–74 years and ≥75 years) using univariable and multivariable analyzes. Eligible patients (n=448) were divided into age cohorts: <65 years (n=185), 65–74 years (n=154) and ≥75 years (n=109). Fewer patients in the oldest cohort (7.3%) received an anti-CTLA4 antibody containing regimen compared with the younger cohorts (21.1% and 17.5%). There was no significant difference overall in all grade or ≥G3 toxicities between age cohorts. Significantly fewer patients in the older (65–74 years and ≥75 years) age cohorts discontinued treatment because of toxicity (10.1% and 7.4%) compared with in the <65 years cohort (20.5%; p=0.006). Using logistic regression, only treatment type (ipilimumab containing) was significantly associated with all grade toxicity. However, there was a significantly lower incidence of all-grade endocrine toxicity in the oldest cohort (11.0%) compared with the youngest cohort (22.7%, p=0.02; OR 0.43, 95% CI 0.21 to 0.87), while all-grade dermatological toxicity showed the reverse trend (28.4% vs 18.9%; OR 1.85, 95% CI 1.04 to 3.30). Results were corroborated in the sensitivity analysis using only data from patients who received PD-1 inhibitor monotherapy. This multicenter, real-world cohort demonstrates that immune checkpoint inhibitor therapy is safe and well tolerated regardless of age, with no appreciable increase in adverse events in older adult patients.